Molecular detection of human enteric viruses circulating among children with acute gastroenteritis in Valencia, Venezuela, before rotavirus vaccine implementation - Ana C. Alcalá (Gut Pathogens, 2018)
Abstract Background The role of rotavirus as main etiologic agent of diarrhea has been well documented worldwide, including in Venezuela. However, information about the prevalence of gastrointestinal viruses such as calicivirus, adenovirus and astrovirus is limited and the contribution of other agents as Aichi virus and klassevirus is largely unknown. To explore the etiological spectrum of diarrhea associated with agents other than rotaviruses, 227 stool samples from children under 5 years old with acute gastroenteritis, collected in Valencia (Venezuela) from 2001 to 2005, and previously tested as rotavirus-negative, were analyzed for caliciviruses, adenoviruses, astroviruses, Aichi viruses, klasseviruses, picobirnaviruses and enteroviruses by specific RT-PCRs. Results At least one viral agent was detected in 134 (59%) of the samples analyzed, mainly from children under 24 months of age and most of them belonging to the lowest socioeconomic status. Overall, enterovirus was identified as the most common viral agent (37.9%), followed by calicivirus (23.3%), adenovirus (11.5%), astrovirus (3.5%), klassevirus (1.3%) and Aichi virus (0.4%), while no picobirnavirus was detected. Klasseviruses were found during 2004 and 2005 and Aichi viruses only in 2005, indicating their circulation in Venezuela; meanwhile, the rest of the viruses were detected during the whole study period. Coinfections with two or more viruses were found in 39 (29.1%) of the infected children, most under 24 months of age. Adenovirus was involved as the coinfecting agent in at least 46.9% of the cases, but no differences concerning socio-demographic variables were observed between the coinfected and the single infected children. Conclusions The results show that various enteric viruses, including enteroviruses, caliciviruses and adenoviruses, accounted for a significant proportion of infantile diarrhea cases in Venezuela before rotavirus vaccine implementation. In addition, emerging viruses as Aichi virus and klassevirus were found, indicating the need to continue monitoring their spreading into the communities. Efforts are needed to develop more accurate methods to identify the major causes of diarrhea and to provide tools for more effective preventive measures.